Photovoltaic Industrial Systems An Environmental Approach - Papadopoulou, Elena; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book investigates the existing situation of photovoltaic systems regarding environmental questions and energy efficiency in the European Industry, particularly the industrial units at the Greek area. A model of energy management based on economical, technical and administrative aspects is proposed in order to combine industrial uses of photovoltaics with environment protection.
Foreword -- Introduction -- Energy Management -- Photovoltaic Energy -- Installed PV System at industrial buildings -- Installation Guide -- Installation of a 20 kW Grid-Connected PV System at the Greek area -- Bibliography -- Appendix.
Keywords: Engineering; Renewable energy sources; Environmental pollution; Technology; Engineering; Renewable and Green Energy; Industrial Pollution Prevention; Technology Management